2010
DOI: 10.1369/jhc.2010.956433
|View full text |Cite
|
Sign up to set email alerts
|

HTII-280, a Biomarker Specific to the Apical Plasma Membrane of Human Lung Alveolar Type II Cells

Abstract: The pulmonary alveolar epithelium is composed of two morphologically distinct cell types, type I (TI) and type II (TII) cells. Alveolar TII cells synthesize, secrete, and recycle surfactant components; contain ion transporters; and secrete immune effector molecules. In response to alveolar injury. TII cells have the capacity to act as progenitor cells, proliferating and transdifferentiating into TI cells. Although various proteins are associated with TII cells, a plasma membrane marker specific to human TII ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 44 publications
7
78
0
Order By: Relevance
“…We have begun to address the question of whether AEC2s from human lungs are also long-term self-renewing stem cells able to give rise to alveolospheres in 3D culture. AEC2s were isolated using FACS based on expression of the surface marker HTII-280 (18). Immunohistochemistry of normal human lungs confirmed that HTII-280 and SFTPC colocalize, with HTII-280 being expressed on the luminal surface and SFTPC in the cytoplasm ( Figure 7A).…”
Section: Sftpc + Cells On the Periphery And Cells With Aec1 Markers Imentioning
confidence: 88%
“…We have begun to address the question of whether AEC2s from human lungs are also long-term self-renewing stem cells able to give rise to alveolospheres in 3D culture. AEC2s were isolated using FACS based on expression of the surface marker HTII-280 (18). Immunohistochemistry of normal human lungs confirmed that HTII-280 and SFTPC colocalize, with HTII-280 being expressed on the luminal surface and SFTPC in the cytoplasm ( Figure 7A).…”
Section: Sftpc + Cells On the Periphery And Cells With Aec1 Markers Imentioning
confidence: 88%
“…After lysing of the red blood cells, AECs were purified through a discontinuous gradient and subsequent positive selection with EpCAM microbeads (Miltenyi Biotec Inc., San Diego, CA). The purity of isolated type II cells was around 90%, as evaluated by staining the cells with pro-SP-C and ATII-280, an ATII-specific marker (14), by flow cytometry (data not shown). The purity was further increased during the primary cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…Type II cells were isolated from donor lungs at 93% purity, as described (2). In some experiments, epithelial cells of adult peripheral lung were isolated by elastase treatment and FACS sorted, as previously described (17). Cells were initially treated with human IgG (50 g/ml; Sigma) to block nonspecific binding of mouse monoclonal primary antibodies against the type II cell-specific HTII-280 protein.…”
Section: Methodsmentioning
confidence: 99%
“…Cytospins of freshly isolated adult type II cells were fixed in 4% paraformaldehyde over night, washed, and stored at ÏȘ20°C until use. Cytospins were permeabilized and stained for CEACAM6 (1:100) and HTII 280, a type II cell-specific marker in human lung (1:200) (17). Adult trachea sections were treated in a similar fashion and stained with CEACAM6 and rabbit anti-pan-cytokeratin (1:100, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%